2005
DOI: 10.1186/1475-925x-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Computational model of blood flow in the aorto-coronary bypass graft

Abstract: BackgroundCoronary artery bypass grafting surgery is an effective treatment modality for patients with severe coronary artery disease. The conduits used during the surgery include both the arterial and venous conduits. Long- term graft patency rate for the internal mammary arterial graft is superior, but the same is not true for the saphenous vein grafts. At 10 years, more than 50% of the vein grafts would have occluded and many of them are diseased. Why do the saphenous vein grafts fail the test of time? Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The process of intimal thickening as a prelude to bypass graft stenosis may be initiated by changes in fluid biomechanical forces sensed by the cells in the graft (18). For example, conduits undergo an acute static-to-shear transition after the reperfu- Ϫ ␣-SM actin ϩ cells reside at the inner surface of human saphenous vein conduits making contact with flowing blood (magnification, 200ϫ).…”
Section: Induction Of C-jun In Smcs Exposed To Fluid Shear Stress Is mentioning
confidence: 99%
“…The process of intimal thickening as a prelude to bypass graft stenosis may be initiated by changes in fluid biomechanical forces sensed by the cells in the graft (18). For example, conduits undergo an acute static-to-shear transition after the reperfu- Ϫ ␣-SM actin ϩ cells reside at the inner surface of human saphenous vein conduits making contact with flowing blood (magnification, 200ϫ).…”
Section: Induction Of C-jun In Smcs Exposed To Fluid Shear Stress Is mentioning
confidence: 99%
“…To evaluate shear stress more accurately, it is necessary to solve the Navier–Stokes equations for the velocity vector ( u ) [ 67 ]. When the blood is assumed to be incompressible ( ρ = constant), the Navier–Stokes equations are described as below: where ρ is the blood density, ν is the kinematic viscosity ( ν = μ / ρ ), and p is the pressure.…”
Section: Physiological and Anatomical Factors Affecting Vein Graft Pamentioning
confidence: 99%
“…The potential for obtaining information helpful in therapeutic decision making was demonstrated by analyzing selected hemodynamic parameters such as blood flow pathlines, wall shear stresses, dynamics pressures, blood flow velocities, and flow particle residence times. Sankaranarayanan et al [ 7 ] transient model of aorta-coronary bypass graft showed that maximum perfusion of the occluded artery occurs during middiastole, and the maximum wall shear stress variation is observed around the distal anastomotic region. Pulsatile flow through a stenosed artery using Casson model for blood was investigated by Sankar and Lee [ 8 ].…”
Section: Introductionmentioning
confidence: 99%